Future climate change will intensify snow drought in the high-latitude water tower, Changbai Mountain - Moran Xu; Haiqing Wang; Shilin Zhang; Yingyi Chen; Yu An; Guangxin Zhang; Peng Qi (Global and Planetary Change, 2026)

Dim moving target detection with hyperspectral image sequences - Xu He; Wei An; Yingqian Wang; Gaowei Guo; Yihang Luo; Qiang Ling; Shilin Zhou (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Alternation magnitudes of organic matter composition determines priming effect of biodegradable microplastics on lake carbon emission - ShengHao Zhang; XiaoZi Chang; FengTing Wu; YueHan Lu; ShiLin An; YongQiang Zhou; MuHua Feng; YingXun Du (Water Research, 2026)

Macrophyte restoration alters sedimentary organic matter-microbes-environment interactions and enhances carbon sequestration in lake sediment - FengTing Wu; ShiLin An; JingJing Liu; YueHan Lu; Hu He; XiaoZi Chang; Qi Leng; ShengHao Zhang; Peng Xing; KuanYi Li; YingXun Du (Water Research, 2026)

Climate-driven hydrological and biogeochemical shifts lead to increasing dissolved organic carbon storage in a Tibetan lake of Nam Co - ShiLin An; Xosé Antón Álvarez-Salgado; FengTing Wu; ShengHao Zhang; Ding He; He Chen; YueHan Lu; YingXun Du; YunLin Zhang (Water Research, 2026)

Authigenic CaCO3 precipitation contributes to the stabilization of algal-derived organic carbon in karst lake - Yingxun Du; Cheng Zhao; Xuexin Han; Shilin An; Zhendu Mao; Fan Xun; Ding He; Yongdong Zhang; Muhua Feng; Wenlei Luo; Qinglong L. Wu; Peng Xing (Water Research, 2025)

Artificial intelligence boosting multi-dimensional information fusion: Data collection, processing and modeling for food quality and safety assessment - Hengrui Zhang; Yuandong Lin; Shilin Cao; Jun-Hu Cheng; Xin-An Zeng (Trends in Food Science & Technology, 2025)

Warming effects on pelagic carbon metabolism is related to substrate composition and bacterioplankton community history - Zhendu Mao; Yixuan Han; Fan Xun; Shilin An; Biao Li; Yujing Wang; He Chen; Qinglong L. Wu; Peng Xing (Water Research, 2025)

Macrophyte Restoration Promotes Lake Microbial Carbon Pump to Enhance Aquatic Carbon Sequestration - He Chen; Peng Xing; Shuhji Kao; Shilin An; Zhendu Mao; Shiming Fan; Biao Li; Qingyun Yan; Qinglong L. Wu (Global Change Biology, 2025)
Macrophyte‐based lake restoration has successfully transitioned lakes from turbid conditions dominated by phytoplankton to a more natural, clear state; however, its impact on microbial carbon pump‐mediated dissolved organic carbon (DOM) storage and greenhouse gas (GHG) emissions in the aquatic ecosystem remains largely unexplored. Through a year‐long field study, we conducted a comparative analysis of two alternative habitats within the same lake—restored and unrestored areas. Results demonstrated that restoration not only substantially decreases nutrient levels and algal blooms—evidenced by over 50% reductions in nitrogen, phosphorus, and chlorophyll a—but also significantly increases the accumulation of recalcitrant DOM. This is characterized by rises of 9.52% in highly unsaturated compounds, 8.68% in carboxyl‐rich alicyclic molecules, 37.54% polycyclic condensed aromatics and polyphenols, and 20.21% in SUVA 254 . Additionallly, key microbial taxa with potent carbon pump functions—primarily Gammaproteobacteria, Alphaproteobacteria, and Actinobacteria—are enriched in restored areas. Structural equation modeling (SEM) further elucidated the complex interrelationships within more pristine lake ecosystems: macrophytes and elevated dissolved oxygen (DO) concentrations enhance carbon sequestration via microbial carbon pump pathways, while the restoration significantly mitigates methane emissions caused by eutrophication. These findings highlight an extra function of aquatic macrophyte restoration, offering valuable insights into microbial processes for future restoration efforts aimed at promoting sustainable aquatic ecosystems and mitigating global warming.

Composition regulates dissolved organic matter adsorption onto iron (oxy)hydroxides and its competition with phosphate: Implications for organic carbon and phosphorus immobilization in lakes - ShuaiLong Wen; JingJing Liu; YueHan Lu; JiaRu Dai; XiuLin Huang; ShiLin An; Erik Jeppesen; ZhengWen Liu; YingXun Du (Journal of Environmental Sciences, 2024)

Sunlight irradiation promotes both the chemodiversity of terrestrial DOM and the biodiversity of bacterial community in a subalpine lake - ShiLin An; ZhenDu Mao; Meilian Chen; XiuLin Huang; LiMei Shi; Peng Xing; LingYang Kong; YongQiang Zhou; YingXun Du; YunLin Zhang (Environmental Research, 2023)

Stability of organic matter-iron-phosphate associations during abiotic reduction of iron - ShuaiLong Wen; YueHan Lu; JiaRu Dai; XiuLin Huang; ShiLin An; JingJing Liu; ZhengWen Liu; YingXun Du; YunLin Zhang (Journal of Hazardous Materials, 2023)

Transformation of algal-dissolved organic matter via sunlight-induced photochemical and microbial processes: interactions between two processes - XiuLin Huang; ShiLin An; Shuo Chen; JiaRu Dai; JingJing Liu; ShuaiLong Wen; TingZhen Li; Peng Xing; YingXun Du (Environmental Science and Pollution Research, 2023)

In-lake processing counteracts the effect of allochthonous input on the composition of color dissolved organic matter in a deep lake - ShiLin An; FeiZhou Chen; Shuo Chen; MuHua Feng; MingLiang Jiang; LiGang Xu; ShuaiLong Wen; QiaoYing Zhang; JinDuo Xu; YingXun Du; YunLin Zhang (Science of The Total Environment, 2023)

Phosphate alters the compositional characteristics of humic acid adsorbed onto goethite - ChunYan Luo; ShuaiLong Wen; ShiLin An; YueHan Lu; YingXun Du (Journal of Soils and Sediments, 2021)

High-mobility group A1 proteins enhance the expression of the oncogenic miR-222 in lung cancer cells - Yunzhi Zhang; Teng Ma; Shuping Yang; Mingying Xia; Jing Xu; Haijia An; Yajun Yang; Shilin Li (Molecular and Cellular Biochemistry, 2011)